Rolling method for obtaining ultrahigh-strength low-oxygen titanium-zirconium alloy

By applying low-oxy titanium zirconium alloys in the dental implant field and adopting specific rolling and heat treatment processes, the problems of insufficient strength and fatigue resistance of traditional titanium zirconium alloys are solved, high strength and good elongation of fracture are achieved, and the needs of dental implant matrix materials are met.

CN119753547AActive Publication Date: 2025-04-04ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411961628.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Traditional titanium zirconium alloys have problems in the field of dental implantation, and titanium alloys with high oxygen content will inhibit twin deformation and affect the break elongation of the alloy.

Method used

The mechanical properties of the alloy are improved through specific rolling and heat treatment processes, including solid solution treatment, water-cooled quenching, pickling, warm rolling, recrystallization annealing and liquid nitrogen cold rolling.

Benefits of technology

The fine grainization and toughening of titanium-zirconium alloy are achieved, the tensile strength and elongation of fracture are improved, and the clinical needs of dental implant matrix materials are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753547A_ABST
    Figure CN119753547A_ABST
Patent Text Reader

Abstract

The invention discloses a rolling method for obtaining an ultrahigh-strength low-oxygen titanium-zirconium alloy. The method comprises the following steps: smelting to obtain a low-oxygen titanium-zirconium alloy; the alloy is subjected to solution treatment and water-cooling quenching; the alloy is subjected to acid pickling to remove surface oxide skin, and cleaning and drying are conducted; carrying out warm rolling on the alloy; carrying out warm rolling on the alloy at a lower temperature, or carrying out liquid nitrogen cold rolling on the alloy after recrystallization annealing, and carrying out stress relief annealing; cleaning and drying the alloy; the alloy is subjected to annealing treatment; and the alloy is cleaned and dried. The process flow provided by the invention is simple and easy to implement, and related equipment and reagents are common and easy to obtain. By using the process method provided by the invention, the low-oxygen titanium-zirconium alloy with excellent strength can be obtained, and the material requirement of the implant tooth matrix in clinical application can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material processing technology, and in particular relates to a rolling method for obtaining an ultra-high strength low-oxygen titanium-zirconium alloy. Background Art

[0002] Titanium-zirconium alloy is a good new implant material. It makes up for the deficiencies in the mechanical properties of pure titanium implants and the deficiencies in the biocompatibility of Ti6Al4V implants, and has a relatively suitable price level. Therefore, it has broad application prospects in the field of oral dental implants.

[0003] In response to the problems of insufficient strength and fatigue fracture resistance of traditional pure titanium implants, binary titanium-zirconium alloys with a Zr content of 14-17wt% have become the preferred material for narrow-diameter implants due to their good mechanical properties, corrosion resistance and biocompatibility. In recent years, oxygen-containing titanium alloys have become a hot topic in the field. The addition of oxygen can have a good strengthening effect on titanium alloys, but a higher content of oxygen will also significantly affect the alloy's elongation at break and severely inhibit twin deformation. In addition to composition regulation, process optimization is also an important way to improve alloy performance. Therefore, it is of great significance to improve the rolling process of low-oxygen titanium-zirconium alloys to further improve the comprehensive mechanical properties of titanium-zirconium alloys and meet clinical requirements. Summary of the invention

[0004] The present invention aims to provide two rolling and heat treatment process flows for obtaining ultra-high strength low-oxygen titanium-zirconium alloy.

[0005] In order to achieve the above-mentioned object, the technical route of the present invention is as follows: As a first aspect, a rolling method for obtaining an ultra-high strength low-oxygen titanium-zirconium alloy is provided, comprising the following steps:

[0006] The titanium-zirconium alloy with an oxygen mass percentage content of ≤0.18% is subjected to a solid solution treatment and water-cooling quenching at 900°C for 0.5h to ensure the uniformity of the structure and composition; the alloy is pickled with an acid etching solution to remove the surface oxide scale, and then cleaned with a cleaning solution and dried;

[0007] The cleaned titanium-zirconium alloy is warm rolled at 500°C; the warm rolled titanium-zirconium alloy is subjected to any of the following treatments until the total reduction ratio is 90%: (1) cold rolling after recrystallization annealing, (2) warm rolling at a temperature below 400°C;

[0008] Annealing is performed at 400°C for 1 hour; cleaning and drying are performed with a cleaning solution.

[0009] The present invention also provides two preferred solutions, one of which is as follows:

[0010] 1) Smelting to obtain low-oxygen titanium-zirconium alloy as process raw material;

[0011] 2) subjecting the titanium-zirconium alloy to solid solution treatment and water cooling quenching;

[0012] 3) pickling the titanium-zirconium alloy with an acid etching solution to remove the surface oxide scale, cleaning it with a cleaning solution and drying it;

[0013] 4) warm rolling the cleaned titanium-zirconium alloy at 500° C. until the reduction rate reaches 75%;

[0014] 5) heat treating the warm-rolled titanium-zirconium alloy at a recrystallization temperature of 750° C. for 1 h;

[0015] 6) cold rolling the recrystallized titanium-zirconium alloy with liquid nitrogen, and annealing the alloy at 400° C. for 1 h each time a certain reduction rate is reached until the reduction rate reaches 60%, thereby obtaining a titanium-zirconium alloy with a total reduction rate of 90% compared to the initial material;

[0016] Among them, before each rolling, the alloy is completely immersed in liquid nitrogen for more than 3 minutes to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to keep the single rolling reduction rate ≤2%. Stress relief annealing is carried out every time the stage reduction rate reaches 20%, and unidirectional rolling is adopted.

[0017] 7) The treated titanium-zirconium alloy is cleaned with a cleaning solution and dried.

[0018] The second one is as follows:

[0019] 1) Smelting to obtain low-oxygen titanium-zirconium alloy as process raw material;

[0020] 2) subjecting the titanium-zirconium alloy to solid solution treatment and water cooling quenching;

[0021] 3) pickling the titanium-zirconium alloy with an acid etching solution to remove the surface oxide scale, cleaning it with a cleaning solution and drying it;

[0022] 4) warm rolling the cleaned titanium-zirconium alloy at 500° C. until the reduction rate reaches 66.7%;

[0023] 5) rolling the warm-rolled titanium-zirconium alloy at a temperature lower than 400° C. (preferably 200° C.) until the reduction rate is 70%, thereby obtaining a titanium-zirconium alloy having a total reduction rate of 90% compared to the initial material;

[0024] Among them, the alloy is kept warm for 5 minutes before each rolling to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to keep the single rolling reduction rate ≤4% until the target reduction rate is reached, and unidirectional rolling is adopted.

[0025] 6) annealing the rolled titanium-zirconium alloy at 400° C. for 1 h;

[0026] 7) The treated titanium-zirconium alloy is cleaned with a cleaning solution and dried.

[0027] In the method, the cleaned titanium-zirconium alloy is warm rolled at 500°C, specifically: the alloy is kept warm for more than 5 minutes before each rolling to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to maintain a single rolling reduction rate of ≤5% until the target reduction rate is reached, and unidirectional rolling is adopted.

[0028] In the low-oxygen titanium-zirconium alloy, the mass percentage of Zr is ≥14% and ≤17%. In the method, the smelting process is as follows: industrial-grade sponge titanium, sponge zirconium and titanium dioxide are used as raw materials, and a vacuum water-cooled copper crucible suspension furnace is used to smelt an ingot, and the ingot is hot-forged to eliminate defects and then wire-cut to obtain an alloy block.

[0029] In the method, the etching solution used for pickling is HF:HNO3:H2O=1:3:16, the cleaning solution is acetone solution, and the cleaning method is ultrasonic cleaning.

[0030] In the method, the annealing process is uniformly kept at 400°C for 1 hour, the purpose of which is to eliminate the residual stress generated inside the alloy during the rolling process and ensure that the rolling is carried out smoothly without fracture. In step 6) of the first technical solution, annealing is performed every time a stage reduction rate of 20% is reached. The calculation method of the stage reduction rate is based on the alloy of the previous stage rather than the alloy in the initial state. A total of 4 annealings are performed, and the reduction rate of the alloy in the liquid nitrogen cold rolling process stage is 60%.

[0031] As a second aspect, the present invention provides a high-strength low-oxygen titanium-zirconium alloy rolled by the method described above, and use thereof in preparing a dental implant matrix.

[0032] The beneficial effects of the present invention are as follows:

[0033] The rolling process flow of the high-strength low-oxygen titanium-zirconium alloy provided by the present invention is simple and clear, easy to implement, and the process equipment and chemicals involved are relatively common and easy to obtain. The process method provided by the present invention can make the titanium-zirconium alloy have fine grains and strengthen the material, meeting the material requirements of the clinical application of dental implant matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention is further described below in conjunction with the accompanying drawings and embodiments;

[0035] Figure 1The raw material of the titanium-zirconium alloy strip has a zirconium content of 16% and an oxygen content of 0.17%. After solution quenching treatment, the unrolled original metallographic structure was photographed using a metallographic microscope.

[0036] Figure 2 The metallographic structure of the titanium-zirconium alloy strip with a zirconium content of 16% and an oxygen content of 0.17% in Example 1 was photographed with a metallographic microscope after being processed by the rolling process of Technical Solution 1 and subjected to a tensile test.

[0037] Figure 3 The metallographic structure of the titanium-zirconium alloy strip with a zirconium content of 16% and an oxygen content of 0.17% in Example 2 was photographed with a metallographic microscope after being processed by the rolling process of Technical Solution 2 and subjected to a tensile test.

[0038] Figure 4 The stress-strain curve is obtained by performing a tensile test on a titanium-zirconium alloy strip having a zirconium content of 16% and an oxygen content of 0.17% as raw material in Example 1 after being processed by the rolling process of Technical Solution 1.

[0039] Figure 5 The stress-strain curve is obtained by performing a tensile test on a titanium-zirconium alloy strip having a zirconium content of 16% and an oxygen content of 0.17% as raw material in Example 2 after being processed by the rolling process of Technical Solution 2. DETAILED DESCRIPTION

[0040] The following will describe in detail the embodiments, features and aspects of the present invention with reference to the accompanying drawings, but the present invention is not limited thereto. Based on any embodiment expanded from the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] The titanium-zirconium alloy strip material used has an element mass percentage of Zr% = 16%, O% = 0.17%, which can be written as Ti-16Zr-0.17O. The instruments used in the rolling process are KQ-50B ultrasonic cleaner, box-type resistance furnace, Nabertherm brick structure muffle furnace, optical metallographic microscope, rolling machine, and tensile testing machine. The titanium-zirconium alloy with an initial thickness of 12 mm is placed in a furnace and subjected to a solid solution treatment at 900°C for 0.5 h, followed by water cooling and quenching to ensure the uniformity of the structure and composition. Subsequently, the surface oxide scale is removed by pickling and corrosion with a corrosive solution with a volume ratio of HF:HNO3:H2O=1:3:16, and the surface oxide scale is cleaned and dried with an acetone solution. The 12 mm titanium-zirconium alloy is then rolled to 3 mm at 500°C, and then placed in a furnace for recrystallization annealing at 750°C for 1 h. After that, the 3mm titanium-zirconium alloy was cold rolled with liquid nitrogen, and after rolling to 2.4mm, 1.9mm, 1.5mm, and 1.2mm, stress relief annealing was performed at 400℃ for 1h to ensure the smooth rolling process and prevent the alloy from being rolled to fracture. The titanium-zirconium alloy after the process was subjected to a tensile test, and the stress-strain curves were as follows: Figure 4 As shown in the figure, while the tensile strength of the material exceeds 1110Mpa, the elongation at break also reaches about 13%, showing excellent mechanical properties. The alloy sample after the tensile test was inlaid and polished to make a metallographic sample, and the metallographic image obtained by metallographic microscope is as follows Figure 2 As shown, it is found that the grains are greatly refined and some twins appear.

[0043] Example 2

[0044] The titanium-zirconium alloy strip material used is Ti-16Zr-0.17O. The instruments used in the rolling process are the same as those described in Example 1. A titanium-zirconium alloy with an initial thickness of 12 mm is placed in a furnace and subjected to a solid solution treatment at 900°C for 0.5 h, followed by water quenching to ensure the uniformity of the structure and composition. Subsequently, the surface oxide scale is removed by pickling and corrosion using a corrosive solution with a volume ratio of HF:HNO3:H2O=1:3:16, and then the surface oxide scale is cleaned and dried with an acetone solution. The 12 mm titanium-zirconium alloy is then rolled to 4 mm at 500°C, and then the 4 mm titanium-zirconium alloy is rolled to 1.2 mm at 200°C, and stress relief annealing is performed at 400°C for 1 h. The titanium-zirconium alloy after the process is subjected to a tensile test, and the stress-strain curve obtained is as shown below. Figure 5 As shown in the figure, while the tensile strength of the material reaches 1030Mpa, the elongation at break also reaches about 15%, showing excellent mechanical properties. The alloy sample after the tensile test is inlaid and polished to make a metallographic sample, and the metallographic image obtained is as follows: Figure 3 As shown, the grains are obviously refined and significantly fragmented.

[0045] The above embodiments are used to illustrate the present invention rather than to limit the present invention. Any modification and change made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A rolling method for obtaining an ultra-high strength low-oxygen titanium-zirconium alloy, characterized in that: The following steps are involved: The titanium-zirconium alloy with an oxygen mass percentage content of ≤0.18% is subjected to a solid solution treatment and water-cooling quenching at 900°C for 0.5h to ensure the uniformity of the structure and composition; the alloy is pickled with an acid etching solution to remove the surface oxide scale, and then cleaned with a cleaning solution and dried; The cleaned titanium-zirconium alloy is warm rolled at 500°C; the warm rolled titanium-zirconium alloy is subjected to any of the following treatments until the total reduction ratio is 90%: (1) cold rolling after recrystallization annealing, (2) warm rolling at a temperature below 400°C; Annealing is performed at 400°C for 1 hour; cleaning and drying are performed with a cleaning solution.

2. The method according to claim 1, characterized in that: In the above (1), cold rolling is performed after recrystallization annealing, specifically: the titanium zirconium alloy that has been warm rolled to a reduction rate of 75% is heat treated and kept at a recrystallization temperature of 750°C for 1 hour; the recrystallized titanium zirconium alloy is cold rolled under the action of liquid nitrogen, and is annealed at 400°C for 1 hour at intervals until the total reduction rate is 90%.

3. The method according to claim 1, characterized in that: In the above (2), warm rolling is performed at a temperature below 400°C, specifically: the titanium-zirconium alloy that has been warm rolled to a reduction rate of 66.7% is rolled at a temperature below 400°C until the total reduction rate is 90%.

4. The method according to claim 1, characterized in that: The volume ratio of the components of the acid etching solution is HF:HNO3:H2O=1:3:16; the cleaning solution is an acetone solution, and the cleaning method is ultrasonic cleaning.

5. The method according to claim 1, characterized in that: The cleaned titanium-zirconium alloy is warm rolled at 500°C, specifically: the alloy is kept warm for more than 5 minutes before each rolling to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to maintain a single rolling reduction rate of ≤5% until the target reduction rate is reached, and unidirectional rolling is adopted.

6. The method according to claim 2, characterized in that: The recrystallized titanium-zirconium alloy is cold rolled under the action of liquid nitrogen, and is annealed at 400°C for 1 hour at intervals for multiple times until the total reduction rate is 90%. Specifically, the alloy is completely immersed in liquid nitrogen for more than 3 minutes before each rolling to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to maintain a single rolling reduction rate of ≤2%. Stress relief annealing is performed every time the stage reduction rate reaches 20%, and unidirectional rolling is adopted.

7. The method according to claim 3, characterized in that: The titanium-zirconium alloy which has been warm-rolled to a reduction rate of 66.7% is rolled at a temperature below 400°C until the total reduction rate is 90%. Specifically, the alloy is kept warm for 5 minutes before each rolling to ensure that the alloy reaches the temperature required by the process, and the roller spacing of the rolling mill is slowly reduced to maintain a single rolling reduction rate of ≤4% until the target reduction rate is reached, and unidirectional rolling is adopted.

8. The method according to claim 1, characterized in that: In the low-oxygen titanium-zirconium alloy, the mass percentage content of Zr is ≥14% and ≤17%.

9. A high-strength low-oxygen titanium-zirconium alloy rolled by the method according to claim 1.

10. Use of the high-strength low-oxygen titanium-zirconium alloy according to claim 9 in preparing a dental implant matrix.

Citation Information

Patent Citations

  • Preparation method of titanium zirconium base alloy

    CN103602840A

  • Treatment process used for improving cold rolling performance of titanium and zirconium alloy high in zirconium content

    CN105734474A

  • Treatment process used for obtaining low-zirconium-content titanium-zirconium alloy perfect recrystallization structure

    CN110042335A

  • Processing technology for improving mechanical property of titanium-zirconium alloy, titanium-zirconium alloy and implant tooth

    CN112553552A

  • Titanium alloy sheet having excellent press formability, method for producing the same, and titanium alloy sheet for heat exchanger

    JP2011046995A